Kepemimpinan Kharismatik dalam Perspektif Pendidikan Islam - Gunawan, Ade; Pratama, Dandy Putra; Hasri, Salfen; Sohiron, Sohiron (Al-Liqo: Jurnal Pendidikan Islam, 2024)
Leaders are easily distinguishable because of their unique combination of skills, experiences, and temperament. Leadership styles have significant effects on the organizations they are used to guide, both positively and negatively. The purpose of this research is to provide a solution to the question of what charismatic leadership means from the viewpoint of Islamic education. Throughout this work, I have relied heavily on research conducted in libraries. Since a qualitative methodology was used, this study falls under the heading of "descriptive research." Following this line of thinking, the charismatic leader places a premium on ideological objectives that connect the group's purpose to the members' long-held beliefs and desires. Leaders who exude charisma have the rare ability to persuade followers to do what they want them to do by appealing to their admiration and esteem. When it comes to spirituality and school administration, the charismatic leadership style is rooted not just on the remarkable traits of trust, authority, and solid belief.